DIRECTORS, PEDAGOGUES AND TEACHERS: KEY INFORMES OF THE INTERDISTS ON SEXUAL DIVERSITY AND HOMOPHOBIA AT SCHOOL - Oliveira Júnior, Isaias Batista de (2019)
The present article presents partial results of an investigation about sexual diversity and homophobia centered in the school. The research was carried out in thirteen public high schools in different districts of the North of Paraná, whose objective was to analyze how the practices of violence attributed to LGBTQIA people are evident in the daily life of the school, through the capture of spontaneous speeches by educators about diversity And homophobia. Methodologically, we used semi-structured interviews with 38 individuals who we consider as key informants, such as directors, pedagogues and teachers. The content analysis was oriented in "who speaks" and "with what purpose it speaks", being that from the interlocuções of the subjects we established categories that were discussed from the Studies of Gender and the Cultural Studies. The main conclusions point out that we are living in a moment in which we are all agents responsible for an egalitarian education, which does not entail the absence of discussions about sexual diversity and strategies for coping with homophobia, and therefore the greatest challenge facing us today Is to open up to this debate.